Strategi Guru Agama Hindu dalam Menginternalisasikan Nilai-Nilai Tri Kaya Parisudha pada Siswa di SDN 3 Sesetan - Widyartha, A. A Gde Rai (Samsara Institute Publisher, 2025)
This study aims to describe the strategies employed by Hindu Religious Education teachers in internalizing the values of Tri Kaya Parisudha among students at SDN 3 Sesetan. Tri Kaya Parisudha, which consists of manacika (right thinking), wacika (right speech), and kayika (right action), is a moral teaching in Hinduism that plays a significant role in character development. The research used a descriptive qualitative method with data collected through observation, interviews, and documentation. The results show that teachers implement several strategies, including integrating Tri Kaya Parisudha values into classroom learning, habituating positive attitudes in the school environment, utilizing moral stories (niti sastra), setting examples through personal conduct, evaluating students’ character, and fostering cooperation with parents and the school community. These strategies have proven effective in cultivating honesty, politeness, responsibility, and empathy among students. Thus, the internalization of Tri Kaya Parisudha values by Hindu Religious Education teachers serves as a fundamental pillar in strengthening students' character from an early age.